Electrochemical Properties and Single Cell Performance of Pd Core-Pt Shell Structured Catalyst Synthesized by a Simple Direct Displacement Reaction. Issue 4 (21st February 2020) - Aoki, Naoya; Inoue, Hideo; Yoshiura, Reiko; Hasegawa, Yuya; Miyazaki, Shunya; Suzuki, Ayono; Daimon, Hideo; Doi, Takayuki; Inaba, Minoru; Higashi, Kotaro; Uruga, Tomoya; Iwasawa, Yasuhiro; et al.
Abstract : A carbon supported Pd core-Pt shell structured catalyst (Pt/Pd/C) was synthesized by a very simple direct displacement reaction (DDR), in which Pd core nanoparticles (NPs) were directly displaced with [PtCl4 ] 2− on stirring in N2 saturated H2 SO4 aqueous solution at 70 °C instead of a modified Cu under potential deposition (Cu-UPD)/Pt displacement method. In DDR, potential difference between Pd core and [PtCl4 ] 2− was decreased compared with the difference between Cu shell and [PtCl4 ] 2− in Cu-UPD/Pt displacement method, which suppressed non-uniform Pt shell formation and increased Pt shell coverage, enhancing oxygen reduction reaction (ORR) activity. Furthermore, fine Pd core NPs were preferentially dissolved out by Cl − anions released from [PtCl4 ] 2− during DDR performed in acidic H2 SO4 solution at 70 °C and mean diameter of Pd@Pt core–shell NPs increased, improving durability of Pt/Pd/C catalyst by the size effect. Large Pd particles, however, were formed in Pt/Pd/C catalyst through a disproportionation reaction of Pd 2+ cations generated in DDR, which was suppressed by addition of Br − anions as complexing agent. A single cell using Pt/Pd/C cathode catalyst synthesized by DDR with Br − anions and activated by H2 –O2 chemical pretreatment showed 2.4-fold ORR mass activity of a commercially available Pt/C catalyst at a current density of 1.0 A cm −2 . Thus, DDR was considered to be a suitable synthetic method for a mass production of highly active and durable Pt/Pd/C catalyst for ORR.